Occupational risk of SARS-CoV-2 infection among healthcare workers in Bangladesh: a multicenter hospital-based study and lessons for future epidemics - Ahamed Khairul Basher; Md Abdullah Al Jubayer Biswas; Aninda Rahman; Mahmudur Rahman; Fahmida Chowdhury; Md. Zakiul Hassan (Tropical Medicine and Health)
Abstract Background Frontline healthcare workers (HCWs) were particularly vulnerable to contracting SARS-CoV-2 infection as a result of occupational exposure. There is a scarcity of data characterizing the risk of SARS-CoV-2 infection among HCWs, particularly in low-income hospital settings. This study aimed to assess the prevalence of COVID-19 among HCWs and identify associated risk factors. Methods From July 2021 to July 2023, we enrolled HCWs from 13 primary, 2 secondary, and five tertiary care hospitals in four selected districts of Bangladesh. We collected information on demography and risk exposure in a face-to-face interview. We calculated the odds ratio to measure the risk using multivariable logistic regression. Results We enrolled 3436 HCWs: 22% (747) physicians, 47% (1632) nurses, and 31% (1057) support staff. Most of the HCWs were female 67% (2292), and the mean age was 38.1, IQR = 29–44 years. Overall, 26% (889) of HCWs had lab-confirmed SARS-CoV-2 infection. Among HCWs, nurses accounted for the highest proportion of COVID-19 infections at 53% (473/1632). Physicians had a significantly higher risk of infection with an aOR of 3.08 (95% CI 2.42–3.93; p < .001) compared to support staff. HCWs who had direct exposure to COVID-19 patients were also at a higher risk, with a 1.93 times higher likelihood of infection ([aOR] = 1.93, 95% CI 1.50–2.47; p < .001), compared to HCWs who were not exposed. Conclusions This study highlights the heightened vulnerability of HCWs to SARS-CoV-2 infection due to occupational exposure and indicates the risk of nosocomial transmission to patients and emphasizes the importance of implementing targeted infection control measures, such as improved workplace safety protocols and comprehensive training to tackle future pandemics of similar traits.